The Effect of Self-assessed Job Security on the Demand for Medical Rehab - Boris Augurzky; Arndt Reichert; Harald Tauchmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
The interdependence of labor market conditions and the demand for health care has been addressed by several theoretical and empirical analyses. We contribute to the debate by empirically examining the effect of a decrease in self-perceived job security on health care utilization. That is, employees at risk of losing their job might postpone or even try not to use non-acute rehab measures in order to reduce their individual risk of being laid off by avoiding absenteeism and signaling good health. We use individual-level data from the German Socioeconomic Panel for the years 2003, 2004, and 2006. The identification strategy rests on an instrumental variable approach where the county unemployment rate and its relative change compared to the previous year serve as instruments for the employees' self-assessed risk of losing their jobs. Contrary to the hypothesis, we have evidence for job insecurity increasing the demand for medical rehab. This finding is robust to various model variants.
Keywords: I11; 330; Rehab; unemployment; health care utilization; job worries; absenteeism; sick leave; Arbeitsplatzsicherung; Meinung; Arbeitslosigkeit; Rehabilitation; Nachfrage; Fehlzeit; Erwerbsunfähigkeit; Deutschland